Flow generators for helmet CPAP: Which to prefer? A bench study. (February 2023) - Privitera, Daniele; Capsoni, Nicolò; Zadek, Francesco; Mazzone, Annamaria; Bellone, Andrea; Fumagalli, Roberto; Langer, Thomas
Abstract: Objective: To assess the different effect of filters' application during helmet-CPAP delivered with three different flow generators on the delivered fresh gas flow, FiO2, and the noise level inside and outside the helmet. Methods: In a bench study, three flow generators (air-oxygen blender, turbine ventilator and Venturi system) were used to generate two different gas flows (60 L/min and 80 L/min), with a fixed FiO2 at 0.6, to perform a helmet-CPAP on a manikin. Three different fixed PEEP valves (7.5, 10, and 12.5 cmH2 O) were applied at the expiratory port. Gas flow, FiO2 and noise were recorded for each Flow-generator/Flow/PEEP combination, first without filter interposition and then after positioning a heat and moister exchanger filter (HMEF) at the helmet inlet port. Results: The application of the HMEF lead to a significant difference in the flow variation among the three flow generators (p < 0.001). Compared to baseline, the highest flow reduction was observed with the VENTURI (−13.4 ± 1.2 %, p < 0.001), a slight increase with the BLENDER (1.2 ± 0.5 %, p < 0.001), whereas no difference was recorded with the TURBINE (0.1 ± 0.6 %, p = 0.12). After HMEF was interposed, a significant FiO2 variation was observed only with VENTURI (11.3 ± 1.8 %, p < 0.001). As for the noise, the TURBINE was the least noisy system, both with and without the filter interposition. Conclusions: Flow generators used to deliver helmet-CPAP have different characteristics and responses to HMEF interposition. Users should be aware of the effects on FiO2 and flow of the different devices in order to make a precise setup of the circuit.